ANALISIS YURIDIS KONTRAK PERJANJIAN TIDAK TERTULIS DALAM PRAKTIK BISNIS DALAM PELAKSANAAN ASAS ITIKAD BAIK PADA TAHAP PRA KONTRAK - Sahira, Aulia; Danoewijaya, Disie Sugihastuti; Lestari, Gita Amelia; Sihombing , Marsaulina A.; Kusnadi , Nandang (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2025)
The principle of good faith is a fundamental aspect of contract law, especially during the pre-contractual stage where parties negotiate and prepare the groundwork for a formal agreement. This paper examines the application of the good faith principle in the pre-contract phase, emphasizing its crucial role in fostering honest, fair, and transparent negotiations. Good faith requires parties to disclose relevant and material information, avoid deceptive practices, and act with integrity throughout the negotiation process. The absence of written agreements or formal contracts does not diminish the necessity for good faith; rather, it increases the importance of trust and ethical conduct to prevent potential disputes. In the context of Indonesian civil law, the good faith principle is explicitly recognized and serves as a legal basis for holding parties accountable for any misconduct or bad faith actions during negotiations. The study highlights that the implementation of good faith at the pre-contractual stage not only reduces the risk of future conflicts but also ensures a balanced and equitable relationship between the parties. Despite challenges in defining the precise boundaries of good faith, its presence is essential for legal certainty and the protection of rights in contractual relationships. Therefore, integrating the good faith principle from the outset of contractual dealings is vital for creating a trustworthy and just business environment.